2018
DOI: 10.1038/s41598-018-32786-4
|View full text |Cite
|
Sign up to set email alerts
|

The lipid mediator lysophosphatidic acid induces folding of disordered peptides with basic amphipathic character into rare conformations

Abstract: Membrane-active, basic amphipathic peptides represent a class of biomolecules with diverse functions. Sequentially close protein segments also show similar behaviour in several ways. Here we investigated the effect of the lipid mediator lysophosphatidic acid (LPA) on the conformation of structurally disordered peptides including extracellular antimicrobial peptides (AMPs), and calmodulin-binding motifs derived from cytosolic and membrane target proteins. The interaction with associated LPA resulted in gain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Compared with anionic lipid DOPG, distinct structural variations caused by uncharged lipid DOPC suggest that charge might play a crucial role in stabilizing the secondary structure of proteins. However, charge distribution along the peptide is also crucial for the interaction between the amyloidogenic peptide and the lipid . Our results also pointed out that CTD of PAP 248‐286 folds mainly to form β‐sheets upon interaction with DOPC.…”
Section: Discussionsupporting
confidence: 56%
“…Compared with anionic lipid DOPG, distinct structural variations caused by uncharged lipid DOPC suggest that charge might play a crucial role in stabilizing the secondary structure of proteins. However, charge distribution along the peptide is also crucial for the interaction between the amyloidogenic peptide and the lipid . Our results also pointed out that CTD of PAP 248‐286 folds mainly to form β‐sheets upon interaction with DOPC.…”
Section: Discussionsupporting
confidence: 56%
“…Although some have intracellular targets, the action mechanism of most AMPs is based on the disruption of cell membranes (Hancock and Sahl, 2006; Ageitos et al ., 2017). This process is often associated with a disorder-to-order conformational transition upon interaction with lipid membranes (Ageitos et al ., 2017), but also observed for interactions with biomacromolecules (Otvos et al ., 2000; Kragol et al ., 2001; Barańska-Rybak et al ., 2005; Bandyopadhyay et al ., 2013), or even smaller compounds such as endogenous metabolites or drug molecules (Zsila et al ., 2017 a , 2017 b , Juhász et al ., 2018). AMPs often show a broad-spectrum activity toward bacteria, viruses, fungi, protozoa, and even cancer cells (Hancock and Sahl, 2006; Hancock et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, very little is explored related to the nature of such AMP interactions. It has recently been demonstrated that some biologically active small molecules, such as therapeutic drugs, azo dyes with sulphonyl groups, endogenous molecules, and lipid mediators, are able to affect the secondary structure of AMPs (Zsila et al ., 2017 a , 2017 b , 2019; Juhász et al ., 2018). These compounds induce a disorder-to-order conformational transition similarly to what is regularly observed for AMP–membrane interactions (Ageitos et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies in our group have suggested that small molecules of both endogenous and synthetic origin can dramatically affect the structures of AMPs, potentially altering their mechanistic function, including their antimicrobial efficiency . Similarly, it has also been observed that several disordered AMP and protein sequences adopt ordered secondary structures induced by the lipid mediator lysophosphatidic acid; this indicates that the presence and use of such interactions might be widespread in organisms, a phenomenon far from being understood.…”
Section: Introductionmentioning
confidence: 99%